2023
DOI: 10.21037/tau-22-864
|View full text |Cite
|
Sign up to set email alerts
|

Lycopene alleviates lipopolysaccharide-induced testicular injury in rats by activating the PPAR signaling pathway to integrate lipid metabolism and the inflammatory response

Abstract: Background: Male fertility can be hampered by systemic and testicular infections and inflammation, which can lead to impaired spermatogenesis that often cannot be reversed by antibiotic treatment. There has been some suggestion that lycopene (LYC) may be useful in the preservation of fertility, although its mechanisms are complex. This current study examined the therapeutic efficacy of LYC on testicular damage and its underlying mechanisms.Methods: Lipopolysaccharide (LPS; 5 mg/kg) was injected intraperitoneal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 44 publications
1
1
0
Order By: Relevance
“…Yin Cheng et al showed that lycopene could reduce the levels of IL-1α, IL-1β, TNF-α, IL-6, and MCP-1 in rats with lipopolysaccharide-induced testicular injury. This is similar to the results of this study [43]. These results indicate that CP had a beneficial effect on testicle inflammation in diabetic rats by reducing the release of pro-inflammatory cytokines.…”
Section: Discussionsupporting
confidence: 92%
“…Yin Cheng et al showed that lycopene could reduce the levels of IL-1α, IL-1β, TNF-α, IL-6, and MCP-1 in rats with lipopolysaccharide-induced testicular injury. This is similar to the results of this study [43]. These results indicate that CP had a beneficial effect on testicle inflammation in diabetic rats by reducing the release of pro-inflammatory cytokines.…”
Section: Discussionsupporting
confidence: 92%
“…In C57BL/6 mice chronically exposed to cigarette smoke for 60 days, lycopene has shown to restore redox status and mitigate hepatic inflammation [ 160 ]. In addition, Li et al [ 161 ] reported that lycopene mitigated the dysregulation of lipid metabolism and the inflammatory response induced by lipopolysaccharide in the rat testes. Thus, evidence is plentiful demonstrating the anti-inflammatory effects of lycopene both in vitro and in vivo .…”
Section: Biological Activities Of Lycopenementioning
confidence: 99%